Surface Failure and Restore of Diamond-Like Carbon Films for Precision Molding Moldes - XIANG Qingyun, DU Zhongyang, WANG Naishuai, WANG Jianqiang, WANG Yongkang, LI Song (Cailiao Baohu)
In order to study the surface failure process of diamond-like carbon films used in precision molding molds and to explore methods for restoring the surface properties of failed films， a hydrogen-free diamond-like carbon (ta-C) film was prepared on a hard alloy mold using magnetic filtered cathode arc equipment， the mold was used to mold glass in a precision molding press.The structural changes of the films undergoing different times of molding were detected by Raman spectroscopy， and the differences in the surface state of ta-C films before molding and after multiple rounds of molding were detected by using a Vickers hardness tester and white light interferometer， so as to evaluate the failure mode of the films in the precision molding process.The results showed that as the number of molding cycles increased， the Raman characteristic peak ratio ID/IG of the ta-C film increased from 0.66 to 2.67， indicating a phase transition from tetrahedral sp3 to triple coordination bonding sp2.After molding， the hardness of the ta-C film decreased by 15.5%， while the surface roughness increased from 0.6 nm to 25.8 nm.The overall uniformity of the film layer decreased.Analysis of the location of film failure anomalies revealed that the phase transition mainly occurred on the outer surface of the film， and the inner structure of the film remained relatively stable during the molding process， and the surface state of the molded ta-C film could be restored by oxygen ion etching.